Kesiapan Usaha Mikro Kecil Menengah Pangan dalam Penerapan ISO 9001:2008 (Studi Kasus di Palu, Sulawesi Tengah) - Tjahja Muhandri; Dian Herawati; Faleh Setia Budi; Lilis Nuraida; Sutrisno Koswara; Afifah Zahra Agista; Yuli Sukmawati (Institut Pertanian Bogor, 2016)
Small and Medium Industries of the Food (Food SME’s) needs to have SNI products to be competitive in the free market era. SNI certificate product can be provided by the certification body, on the condition that the industry has to implement ISO 9001. This activity aims to identify the readiness of small industries (food) to meet the clauses of ISO 9001 and assist them in improving the necessary documents. Activities carried out for 2 months with 24 samples of small industries (food) in Palu (Central Sulawesi) were selected purposively. The results showed that all the small industries yet to implement all aspects of GMP. Small industry best only meet 21% of the clauses of ISO 9001. Compliance with the clauses of ISO 9001 increased by between 4586% after mentoring.